Dévolution et politiques de santé en Écosse : un modèle de continuité et d'efficacité ? - Edwige Camp-Pietrain (Revue Française de Civilisation Britannique)
Since 1999, Scotland's Parliament and government have striven to improve the health of the Scottish people by restoring a public service based on co-operation and not on competition, while devising policies aimed at modifying the behaviour of individuals. Even though they have achieved some success, they have proved unable to avoid politicizing the issue. Tensions have been fuelled by tighter budgetary constraints and constitutional upheavals.